PENGUKURAN DAN PEMETAAN BIDANG TANAH MENGGUNAKAN METODE EKSTRATERESTRIS DI DESA RIDAN PERMAI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Farouki Dinda Rassarandi; Firmanda; Hafidzur Rosyad Al Makhi An Nusuki (Politeknik Caltex Riau, 2021)
Measurement and mapping of land parcels is one of a series of activities in land registration. This activity is carried out by measuring and mapping at the boundaries of parcels using the extra terrestrial, terrestrial, photogrammetric, remote sensing, and other methods. However, with the progress and development of science and technology at this time, the activity of measuring and mapping land parcels can be done using extrateristris methods using GPS receivers that have high accuracy in a relatively shorttime. Mapping measurements in this study use the method of extraterrestrial. Extraterrestrial is the determination of the position carried out by measurements or observations to objects / celestial bodies both natural (such as the moon, stars and quasars) or man-made such as satellites. One of the methods of extraterrestrial positioning system that has been known so far is survey with GPS. In the end of the measurement of this mapping will produce output in the form of a Peta Bidang Tanah (PBT). PBT are the results of mapping 1 (one) or more parcels of land on paper sheets with a certain scale whose limits have been determined by the authorized official and are used to announcement of physical data.